2019
DOI: 10.1038/s41467-019-10239-4
|View full text |Cite
|
Sign up to set email alerts
|

iSuRe-Cre is a genetic tool to reliably induce and report Cre-dependent genetic modifications

Abstract: Most biomedical research aimed at understanding gene function uses the Cre-Lox system, which consists of the Cre recombinase-dependent deletion of genes containing LoxP sites. This system enables conditional genetic modifications because the expression and activity of the recombinase Cre/CreERT2 can be regulated in space by tissue-specific promoters and in time by the ligand tamoxifen. Since the precise Cre-Lox recombination event is invisible, methods were developed to report Cre activity and are widely used.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
73
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(76 citation statements)
references
References 50 publications
2
73
1
Order By: Relevance
“…However, since there is no genetic linkage between the reporter allele and any other floxed alleles in the cell, the correlation between the recombination of a reporter allele and another floxed allele is often very low. Indeed a recent study showed that some commonly used Rosa26 reporter alleles overreport genetic deletions, whereas others underreport (Fernández-Chacón et al, 2019). In our hands, the commonly used R26-LSL-YFP allele (Srinivas et al, 2001), and particularly the R26-LSL-tdTomato reporter allele (Madisen et al, 2010), are extremely sensitive to Cre/CreERT2 activity, unlike the majority of other tested floxed genes (Fernández-Chacón et al, 2019).…”
Section: Using Recombinase Technology To Study Cardiovascular Gene Fumentioning
confidence: 47%
“…However, since there is no genetic linkage between the reporter allele and any other floxed alleles in the cell, the correlation between the recombination of a reporter allele and another floxed allele is often very low. Indeed a recent study showed that some commonly used Rosa26 reporter alleles overreport genetic deletions, whereas others underreport (Fernández-Chacón et al, 2019). In our hands, the commonly used R26-LSL-YFP allele (Srinivas et al, 2001), and particularly the R26-LSL-tdTomato reporter allele (Madisen et al, 2010), are extremely sensitive to Cre/CreERT2 activity, unlike the majority of other tested floxed genes (Fernández-Chacón et al, 2019).…”
Section: Using Recombinase Technology To Study Cardiovascular Gene Fumentioning
confidence: 47%
“…7c, 7d), we first hypothesized that the survival of Mycn iEC-KO adults and their lack of hematopoietic defects was due to incomplete expression of Tie2-Cre (as shown in Fig1e, 1f) and incomplete Mycn deletion in aortic ECs during EHT. To exclude this possibility that blood in Mycn iEC-KO adults derives from wildtype DA EHT events, we crossed Mycn iEC-KO mice with iSuRe-Cre mice, in which cells expressing MbTomato-2A-Int-Cre have full deletion of any floxed allele 58 . Surprisingly, adult Mycn iEC-KO iSuRe-Cre and control Tie2-Cre iSuRe-Cre mice had similar numbers of Tomato-2A-Cre+ hematopoietic cells (Fig.…”
Section: Mycn and Myc Functions Are Required Sequentially During Embrmentioning
confidence: 99%
“…While the mouse’s physiology does not fully mimic that of human, the generation of whole-body gene KOs and of tissue conditional knockouts (cKOs) in this species has led to countless discoveries 3 , 4 . The traditional, more cumbersome methods of generating mouse models by gene targeting embryonic stem cells 5 , 6 have been mostly replaced by highly precise gene editing technology that inserts loxP sites flanking an essential DNA fragment of the target gene and make it available to a Cre-recombinase for its targeted mutation 7 , 8 . This gene editing system, termed clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR associated protein (Cas9) further allows the precise insertion of exogenous DNA sequences.…”
Section: Introductionmentioning
confidence: 99%